British Colonialism and Och’otukpo in Idomaland, 1927-1949 - Isaac Ogbogo, Ediba (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The advent of the British colonialism in Otukpo District of Idomaland radically transformed the society and opened a new phase in the political and administrative landscape of the area. Aside suppressing and conquering the hitherto independent polity and establishing their administration, the imperialists presented an untrue picture of the society as one which was in dire need of political restoration in view of the perceived political vacuum inherent in Otukpo. This blatant misapplication and distortion of the actual situation in Otukpo became a justification for the overthrow of the indigenous political system of the Och’Otukpo (King of Otukpo) and its subsequent replacement with an alien political system through which the aims and objectives of British colonialism were conveniently implemented. This paper discusses the historical development of this phenomenon and argues that colonialism was a violent phenomenon that punctured the indigenous political systems of Nigerian societies in line with their imperial convictions geared towards deepening their hold of Nigerian societies and facilitating the exploitation of their societies. The paper adopts the historical methodology with emphasis on primary and secondary sources, based on the Marxist theoretical framework which is reflected in the analysis of the paper while the descriptive and analytical modes of research were utilized.